2002
DOI: 10.1093/carcin/23.8.1327
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits the growth and induces the apoptosis of both normal and leukemic hematopoietic cells

Abstract: It is often postulated that trans-3,4',5-trihydroxystilbene (resveratrol, RES) exhibits cell growth regulatory and chemopreventive activities. However, mechanisms by which this polyphenol inhibits tumor cell growth, and its therapeutic potential are poorly understood. Using various human leukemia cells, we have first defined the anti-tumoral doses of this compound. RES inhibited the proliferation and induced the apoptosis of all tested lymphoid and myeloid leukemia cells with IC 50 ⍧ 5-43 µM. Prior to apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 32 publications
7
101
0
Order By: Relevance
“…However, we found the cytotoxicity of TSO in the RAW 264.7 macrophages to be notably less than that of the hydroxylated stilbenes. Although the present study did not determine the type of death incurred by macrophages treated by PIC, RES, or TPS, previous reports have shown that these stilbenes, in particular, can kill other types of cells by apoptosis [14,17,20]. Currently, our lab is exploring the exact mechanism through which the macrophages are dying and this subject will be communicated in a future manuscript relating to this topic.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, we found the cytotoxicity of TSO in the RAW 264.7 macrophages to be notably less than that of the hydroxylated stilbenes. Although the present study did not determine the type of death incurred by macrophages treated by PIC, RES, or TPS, previous reports have shown that these stilbenes, in particular, can kill other types of cells by apoptosis [14,17,20]. Currently, our lab is exploring the exact mechanism through which the macrophages are dying and this subject will be communicated in a future manuscript relating to this topic.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to their antioxidant properties, it is worthy to note that cytotoxic effects of RES, PIC, and TPS have also been reported. In this regard, RES has demonstrated pro-oxidant, genitourinary, immunotoxic, hepatotoxic and genotoxic properties [18][19][20][21][22][23]. PIC, a metabolite of RES, has been reported to induce apoptosis of transformed and primary lymphocytes [17] and to also exhibit cytotoxic actions towards macrophages in vitro [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, resveratrol-treated cells were shown to have a low level of cdk7 kinase-Thr (161)-phosphorylated cdk1 [168]. In vitro and in vivo studies show that resveratrolinduced cell cycle arrest in G2/M phase is associated with an accumulation of cyclins A and B [157,164,169,170] …”
Section: Iii) Resveratrol and G2/m-phase Arrestmentioning
confidence: 99%
“…7,8 It is very well known that resveratrol shows antioxidant, cardioprotective, chemopreventive, anticarcinogenic, antiproliferative and anti-inflammatory effects both in vivo and in vitro. 9,10 Resveratrol has been shown to induce apoptosis in a variety of cancers such as chronic myeloid leukemia (CML), acute myeloid leukemia (AML), breast, prostate, colon and lung cancers. [11][12][13] The exact mechanism of resveratrol mediated anticancer effect is not fully identified.…”
Section: Introductionmentioning
confidence: 99%